Woody plants diversity and the associated provisioning ecosystem services across three contrasting forest management regimes in Southwest Ethiopia - Kebebew, Zerihun; Ozanne, Claire (Frontiers in Conservation Science, 2024)
Woody plants are a source of provisioning ecosystem services. Coffee management impacted forest composition, structure and diversity. We studied the effect of coffee management intensification on woody plants and their associated provisioning ecosystem services under three contrasting forest management regimes in southwest Ethiopia. The study employed mixed approaches (vegetation assessment and ethnoecological study) to collect the data. Woody plants were collected from 189 plots, whereas, perceived local ecosystem services were identified by 136 individuals through an ethnoecological approach. The total number of woody plants recorded in the natural forest, coffee forest and coffee agroforest was 971, 945 and 521 respectively.Species richness in natural forest, coffee forest and coffee agroforest were 57, 54 and 53 respectively. The local people perceived 17 different provisioning ecosystem services collected from the three forest types. The result showed that there is a positive relationship between the diversity and use value of woody plants across the three forest management regimes. Coffee management intensification simplifies the stand structure, woody plant composition and ecosystem services of the forest. Plant use value increases towards coffee agroforest. Coffee agroforest can serve as repository of diversity and ecosystem services in southwest Ethiopia.